SOSIALISASI TIPS DAN TRIK PENERAPAN DIGITAL MARKETING PADA SEBUAH PRODUK USAHA DI RPTRA KOMANDO CERIA, KELURAHAN GALUR, JAKARTA PUSAT - Ana Chaerunisyah; Iin Andaryati; Sri Susanti Widyasari; Achmad Barlian; Muh.Ali Maskur (Batara Wisnu : Indonesian Journal of Community Services, 2023)
In the modern era, the presence of marketing innovations through digital media such as online stores and social media is crucial for local entrepreneurs, especially the PKK mothers and residents of Galur Subdistrict, Central Jakarta. However, many of them still lack a deep understanding of how to effectively utilize digital media to market their products. Through a community service activity titled "Socialization of Tips and Tricks for Implementing Digital Marketing on a Business Product," the community service team employs an educational and participatory approach to enhance understanding of effective digital marketing concepts. Additionally, the aim is to introduce online media that can be used as access for promoting business products and provide tips and tricks for starting digital marketing. The results of this socialization show an improvement in participants' understanding, especially in utilizing social media as the primary promotional tool, opening new opportunities for local entrepreneurs to maximize economic potential through digital platforms. In conclusion, the Socialization of Tips and Tricks for Implementing Digital Marketing on a Business Product can significantly benefit local business actors. This socialization can help expand market reach, increase sales, and enhance the competitiveness of their businesses